Anodic pine cone-like WO3/MoO3/TiO2 film with well-defined nanoflakes on Ti–6Al–7Nb implant - Rafieerad, Ali Reza; Bushroa, Abdul Razak; Nasiri-Tabrizi, Bahman; Amiri, Ahmad; Yusof, Farazila; Vadivelu, Jamuna; Basirun, Wan Jefrey (Springer, 2018)
A pine cone-shaped tungsten−molybdenum−titanium oxides combinatorial coating was successfully grown on Ti–6Al–7Nb implant (Ti67) by a combined approach of RF/DC physical vapor deposition (PVD) and one-pot anodization. The results indicated that the surface morphology and the phase composition were significantly changed as a function of sputtering target and anodization period. Prior to anodization, PVD coating process resulted in the formation of crystalline mono- and multi-layer Mo and Mo/W thin films. After anodization for 60 min, a crystalline mixed oxide structure was formed as a result of oncoming electrochemical reactions. Compared to a single bare substrate and as-sputtered Mo/W multi-layer coating, the 60-min-anodized specimen had the highest hydrophilicity as well as Vickers hardness and showed adhesion strength of around 397 ± 1 MPa. Remarkably, the proposed modification is not only limited to Mo/W multi-layer coating, but can also be employed to a wide range of other transition metals to form a mixed oxide mono-layer on the surface of medical-grade titanium alloys for potential biomedical applications.